The Reliable Application of Fingerprint Evidence - Garrett, Brandon L. (2018)
In November 2017, a state appellate court did something almost unprecedented: It held that a trial judge made an error by admitting testimony on latent fingerprinting. In State v. McPhaul, the North Carolina appellate panel found error in admitting expert testimony, based on the lack of evidence that the expert reliably reached conclusions about the fingerprint evidence. The panel did not reverse the defendant's conviction, however, finding the error to be harmless. The ruling has broader significance for as-applied challenges to the forensic testimony commonly used in criminal cases, in which judges have often not carefully examined reliability either for many forensic methods in general, or how they are applied in a given case. Many forensic techniques rely on the subjective judgment of an expert, who may not be able to fully explain how they concluded that a fingerprint, ballistics, or other types of pattern evidence is a match, except to cite to their own judgment and experience. In this essay, I describe the scientific status of fingerprint evidence, the facts and the judicial reasoning in McPhaul, and the implications of the decision. This sleeper ruling should awaken interest in the reliable application of forensic methods in individual cases